Back to the future: towards the realization of lithium metal batteries using liquid and solid electrolytes - Al-Salih, Hilal; Khan, Hafsah A.; Baranova, Elena A.; Abu-Lebdeh, Yaser (Frontiers in Energy Research, 2023)
As the specific energy of traditional lithium-ion batteries (LIBs) approaches theoretical limits, the quest for alternatives intensifies. Lithium metal batteries (LMBs) stand out as a potential solution, promising substantially higher energy densities (∼35% increase in specific energy and ∼50% increase in energy density at the cell level). Historically, challenges with liquid electrolytes (LEs) in LMBs, such as dendrite growth and unstable solid electrolyte interphase (SEI) formation, led to skepticism about their compatibility and most of the focus was on solid-state electrolytes (SSEs) such as polymer electrolytes and recently inorganic electrolytes (oxides, sulphides halides). However, recent strides in LE engineering have repositioned LEs as viable candidates for LMBs, particularly with the strategic use of additives and the careful formulating of solvents. This review delves into the engineering of LEs for LMBs, highlighting their renewed potential and explores the realm of SSEs and report on the recent advancements in both fields. We aim to provide a comprehensive overview of the evolving landscape of LMB research.